"The Rulings Concerning Foundlings in Islamic Jurisprudence: A Comparative Jurisprudential Study" (Al-Farooq Journal of Sciences, 2026)
This research examines the rulings concerning foundlings in Islamic jurisprudence through a comparative juristic study of the four schools of Islamic law. It clarifies the linguistic and technical meaning of a foundling, the ruling on taking and caring for the child, guardianship, lineage, religion, and social and financial rights. The study aims to highlight Islamic law’s concern for preserving life, lineage, and human dignity, and to explain the legal foundations that guarantee the foundling’s right to life, care, education, financial support, and protection from discrimination. The research adopts the inductive analytical method and the comparative method to present jurists’ opinions and identify areas of agreement and disagreement. It concludes that taking in a foundling is a collective obligation, becoming an individual obligation when the child’s life is at risk, and that guardianship belongs to the ruler or his representative.
Keywords: Foundling, Islamic jurisprudence, guardianship, lineage, objectives of Islamic law.